Cross-border shopping and tax structure - Vidar Christiansen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
A simple benchmark case is established to derive the optimum commodity tax on an externality-generating good that may be purchased abroad directly by domestic consumers. As the tax should under-cut the Pigovian level, this simple case supports the intuition that taxes should be moderated when commodities are cross-border traded. The analysis is extended in two directions. i) It is demonstrated that a fiscal tax, levied on a cross-border traded good, has more complex effects, weakening, or conceivably eliminating, the case for lowering the tax in response to cross-border shopping. Even if a tax cut alleviates distortions in favour of cross-border shopping, it would also induce a further distortion of consumption in the border region. ii) It is shown that when considering the taxation of more than one commodity purchased abroad, we should not neglect joint purchases, as done in previous research. To contain cross-border shopping it may be the more efficient reform to lower the tax on a commodity that is purchased only partially abroad.
Keywords: 330; political economy; redistribution; information; Grenzüberschreitender Güterverkehr; Optimale Besteuerung